Regium@Lepidi 2200 Project - Maurizio Forte (Archeomatica, 2015)
Regium@Lepidi 2200 is an internationalproject designed with the scope to study and virtually reconstruct the Roman city of Regium Lepidi (Reggio Emilia). The final aim is the creation of a new virtual museum and IT room designed within the archaeological museum of Reggio Emilia.